Rewilding the Sea? A Rapid, Low Cost Model for Valuing the Ecosystem Service Benefits of Kelp Forest Recovery Based on Existing Valuations and Benefit Transfers - Williams, Chris; Rees, Sian; Sheehan, Emma V.; Ashley, Matthew; Davies, William (Frontiers in Ecology and Evolution, 2022)
Kelp forests and seagrasses are important carbon sinks that are declining globally. Rewilding the sea, through restoring these crucial habitats, their related biodiversity and ecosystem contributions, is a movement and concept, gathering pace in the United Kingdom and globally. Yet understanding of the economic costs and benefits for setting areas of the sea aside—and removing some human impacts from them—is not well understood. The potential benefits and distributional impacts on marine users and wider society is critical to make evidence based decisions. Ensuring that areas of the sea recover, and that the impacts (both positive and negative) are understood, requires targeted research to help guide decisions to optimize the opportunity of recovery, while minimizing any negative impacts on sea users and coastal communities. We approach the problem from an ecosystem services perspective, looking at the opportunity of restoring a kelp bed in Sussex by removing fishing activity from areas historically covered in kelp. Development of an ecosystem services valuation model showed restoring kelp to its highest mapped past extent (96% greater, recorded in 1987) would deliver a range of benefits valued at over £ 3.5 million GBP. The application of an ecosystem services approach enabled the full range of benefits from habitat restoration to be assessed. The results and the gaps identified in site specific data and values for this area, have broader implications in fisheries management and natural resource management tools for restoring marine habitats and ecosystems in the United Kingdom.